Highly Versatile Preparation of Imidazo[1,5-a]quinolines and Characterization of Their Photoluminescent Properties - Kulhanek, Niclas; Martin, Niklas; Göttlich, Richard; Justus Liebig University Giessen (My University, 2024)
In this work, we describe a simple and robust synthetic approach for the formation of 1,3-substituted imidazo[1,5-a]quinolines. This was achieved by developing a mild and selective bromination with N-bromosuccinimide (NBS) in 3-position of the imidazole ring. This was followed by a Negishi coupling, which we performed with various coupling partners, resulting in a wide range of different combinations, usually unattainable by other approaches and similar coupling reactions. Fluorescence measurements identified beneficial substitution patterns for the future use of imidazo[1,5-a]quinolines in optical applications, such as organic light-emitting diodes (OLEDs).
Keywords: ddc:540